Effects of Different Particle Sizes of Hydroxyapatite on the Distribution and Migration of Trace Elements (Copper and Cadmium) in a Smelter-Impacted Soil. (19th October 2021) - Xu, Lei; Xing, Xiangyu; Zhu, Zhenqiu; Cui, Hongbiao; Peng, Jianbiao; Li, Ding; Ji, Mingfei; Zhou, Jing
Abstract : To study the remediation effect of hydroxyapatite with different particle sizes, a field in situ experiment was carried out by adding conventional hydroxyapatite (0.25 mm) and microhydroxyapatite (3  μ m) and nanohydroxyapatite (40 nm) to the contaminated soil and planting Elsholtzia splendens . The distribution and migration of copper (Cu) and cadmium (Cd) in soil were investigated after 4 years. The results show that the application of three different particle sizes of hydroxyapatite significantly raise the soil pH, total phosphorus, and soil organic carbon. Moreover, the addition of hydroxyapatite can reduce the EXC fraction of Cu and Cd by 73.7%–80.1% and 20.8%–35.2%, respectively. In addition, the concentrations of Cu and Cd in >2 mm, 0.25–2 mm, 0.053–0.25 mm, and <0.053 mm aggregate are significantly increased. This improvement indicates that there are risks which may cause the increasing of total Cu and Cd in the soil where the pollution sources still exist. Furthermore, the content of soil colloid is significantly increased, and the colloidal Cu and Cd distribution percentage have been significantly increased by 49.9%–120% and 30.3%–181%. This result illustrates that the application of hydroxyapatite may greatly increase the possibility of colloid and dust migration of Cu and Cd.